Purchasing Massive Prestige Brands: The Exploration of Consumers’ Value Perceptions - Mayasari, Iin; Wiadi, Iyus (ASEAN Marketing Journal, 2021)
The objective of the research was to analyze the internal aspects of individual consumer to perceive the massive prestige brands. The brand chosen was influenced by conspicuousness, uniqueness, functional value, extended-self, hedonism, exploration, value consciousness, vanity. The research used quantitative approach by conducting a survey college students, workers and housewives. A total of 300 questionnaires were distributed, but only 243 questionnaires were used for further analysis. The data were analyzed by multiple regressions. Conspicuousness consumption had an effect on purchasing of massive prestige brands positively and it was significant. Uniqueness had an effect on purchasing of massive prestige brands positively but it was not significant. Extended-self had an effect on purchasing of massive prestige brands positively and but it was not significant. Hedonism had an effect on purchasing of massive prestige brands positively and it was significant. Exploration had an effect on purchasing of massive prestige brands positively and it was significant. Consciousness value had an effect on purchasing of massive prestige brands negatively and it was significant. Vanity had an effect on purchasing of massive prestige brands positively and it was significant.